New occurence of woolly cupgrass (Eriochloa villosa [Thunb.] Kunth) in Hajdúság area, East-Hungary - Szilágyi, Arnold; Tóth, Tamás; Radócz, László (Acta Agraria Debreceniensis, 2017)
Because of the globalization and global warming the emergence of invasive weeds in Hungary are more common. The woolly cupgrass (Eriochloa villosa [Thunb.] Kunth) is published as an important invasive weed in Hungary. Woolly cupgrass is native in East Asia and it spreads into several parts of the World and causes difficulties in plant protection. It has been spreading extensively during the last few years,as the weed shows a very serious invasion potential.